Disseminated Nocardia cyriacigeorgia causing pancreatitis in a haploidentical stem cell transplant recipient. (2017) - Chen, Jason; Pan, Jonathan; Filicko-O'Hara, Joanne; Kasner, Margaret; Flomenberg, Phyllis
Abstract: We report the first published case of acute pancreatitis secondary to disseminated nocardiosis in a hematopoietic stem cell transplant (HSCT) recipient on chronic immunosuppression for graft-versus-host disease (GVHD). Nocardiosis in the HSCT population is relatively rare, and has not yet been described in haploidentical HSCT recipients. Our patient is a 28-year-old male with a history of haploidentical HSCT and GVHD of the skin and lung who was admitted to the hospital with acute pancreatitis. The workup for the etiology of his pancreatitis was initially unrevealing. He subsequently developed worsening sepsis and respiratory failure despite broad spectrum antimicrobials. After multiple bronchoscopies and pancreatic fluid sampling, he was found to have disseminated nocardiosis with Nocardia cyriacigeorgia .